Efektifitas Pendekatan Analisis Transaksional Berbasis Kato Nan Ampek Untuk Meningkatkan Komunikasi Interpersonal Siswa (JURKAM: Jurnal Konseling Andi Matappa, 2021)
The main problem in this research is the low interpersonal communication skills of students of MAN 3 Tanah Datar. The purpose of this study is to reveal empirical data about the effectiveness of group counseling based on Kato Nan Ampek transactional analysis to improve students' interpersonal communication skills in MAN 3 Tanah Datar. This type of research is quantitative research with experimental research methods, with a quasi experimental research design. Data Analysis Techniques Before the t test is carried out, the normality and homogeneity tests are first carried out with SPSS version 21.00. obtained quantitative data with a value of sig
Keywords: Group Guidance; Transactional Analysis; Kato Nan Ampek; Interpersonal Communication